Isolation, Identification and Sensitivity of Escherichia Coli from Fresh Vegetables in Zawia and Surman City, Libya (Journal of Humanitarian and Applied Sciences, 2023)
In Libya, ready to eat (RTE) vegetables are most used at restaurants and home. Therefore, it is very important to examine possible Escherichia coli (E. coli) contamination in RTE vegetables. This study aimed to isolate E. coli from RTE Vegetables. The antimicrobial sensitivity of E. coli obtained from RTE vegetables was as well performed using 6 usually used antibiotics. Three samples (Lettuce, watercress, and parsley) were collected from Zawia and Surman cities, using media of MacConkey agar and nutrient agar. These samples were analyzed to detect the presence of E. coli. Identification and characterization of E. coli isolates were performed using analytical profile index ABI 20 E. Using the Kirby-Bauer disc diffusion method, antimicrobial susceptibility was determined. Thirty-five (58.3%) of samples showed a positive result of the presence of E. coli, highest percentage (42.86%) was isolated from watercress followed by parsley and lettuce (28.57%) for each one. Highest percentage (71.4%) was isolated from Zawia City, while the lowest percentage (28.6%) was isolated from Surman City. The findings revealed that 35 isolates (100%) were resistant to Augmentin and five isolates (14.29%) were resistant to Amikacin as well.                                                                                                          This revealed that 58.3% of RTE vegetable samples were contaminated with E. coli and the isolates highly resistant to Augmentin (100%) could be hazardous for community health.
Keywords: Antimicrobial sensitivity; Escherichia coli; vegetable